Karakteristik produk body lotion dari nanopartikel kitosan dan alginat (Sargassum sp.): Karakteristik produk body lotion dari nanopartikel kitosan dan alginat (Sargassum sp.) - Sipahutar, Yuliati Hotmauli; Prayudi, Adham; Handoko, Yudi Prasetyo; Lisandry, Marwanti; Sayuti, Mohammad; Siregar, Arpan Nasri; Samanta, Pinki Natalia; Sitorus, Paulus Pardamean Rinaldo (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Chitosan and alginate have great potential in the cosmetics industry; therefore, both were processed into chitosan alginate nanoparticles and added to body lotion formulas to increase their effectiveness. This study aimed to investigate the effect of chitosan alginate nanoparticles on the characteristics and antioxidant activity of body lotions. Body lotion formulas with additional concentrations of 0, 1, 2, and 3 g of chitosan alginate nanoparticles. This study used a completely randomized design (CRD) with chitosan alginate nanoparticle concentrations of 0, 1, 2, and 3 g. The body lotion appeared homogeneous, with no clumped particles. The characteristics of body lotion with the addition of chitosan-alginate nanoparticles are viscosity of 4596.73-6931.77 cps, spreadability of 52.4-68.9 cm, and pH value of 6.00-6.98 which are in accordance with body lotion standards. The antioxidant activity was 19.82-21.59 µM Fe². The addition of chitosan-alginate nanoparticles with particle sizes of 100-500 nm to body lotion increased the antioxidant activity.